Handbook of research on approaches to alternative entrepreneurship opportunities - Dantas, Jose Guilherme Leitao, 1955-; Carvalho, Luísa Cagica, 1970- (Advances in business strategy and competitive advantage., 2020)
"This book explores key developments in entrepreneurship types such as academic entrepreneurship, corporate entrepreneurship, cultural entrepreneurship, and entrepreneurship in high-tech sectors"--